2021
DOI: 10.3311/pptr.16506
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Double Continuous Flow Intersection in Riyadh

Abstract: The continuous growth of population in the capital, coupled with increased auto ownership and dependence has worsened traffic conditions on Riyadh's road network. Conventional methods to address this increased demand could be costly and insufficient. There has been greater interest in using alternative measures to improve the performance and safety characteristics on main corridors, particularly those that arrive at signalized intersections. Heavy left turning traffic at these intersections is one of the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…To improve the operational and safety characteristics of an existing major signalized arterial intersection in Saudi Arabia, a work investigated the efficiency of implementing an unconventional intersection design, the Double Continuous Flow Intersection (DCFI) configuration. The study found that the proposed DCFI unconventional intersection design decreased the average delay per vehicle by 99 seconds and improved the Level of Service at the intersection from level F (152 s/vehicle average delay) to level D (53 s/vehicle average delay) (Bashir et al, 2021). The safety performance of the new mega elliptical roundabout interchange was analyzed and compared with eight other interchange designs and it was concluded that the mega elliptical roundabout interchange has good safety performance compared to other interchanges studied by (Mane and Pulugurtha, 2020).…”
Section: Literature Reviewmentioning
confidence: 98%
“…To improve the operational and safety characteristics of an existing major signalized arterial intersection in Saudi Arabia, a work investigated the efficiency of implementing an unconventional intersection design, the Double Continuous Flow Intersection (DCFI) configuration. The study found that the proposed DCFI unconventional intersection design decreased the average delay per vehicle by 99 seconds and improved the Level of Service at the intersection from level F (152 s/vehicle average delay) to level D (53 s/vehicle average delay) (Bashir et al, 2021). The safety performance of the new mega elliptical roundabout interchange was analyzed and compared with eight other interchange designs and it was concluded that the mega elliptical roundabout interchange has good safety performance compared to other interchanges studied by (Mane and Pulugurtha, 2020).…”
Section: Literature Reviewmentioning
confidence: 98%